Influenza economic burden among potential target risk groups for immunization in South Africa, 2013–2015. Issue 45 (21st October 2020) - Tempia, Stefano; Moyes, Jocelyn; Cohen, Adam L.; Walaza, Sibongile; McMorrow, Meredith L.; Edoka, Ijeoma; Fraser, Heather; Treurnicht, Florette K.; Hellferscee, Orienka; Wolter, Nicole; von Gottberg, Anne; McAnerney, Johanna M.; et al.
Highlights: Influenza-associated illness cost among risk groups is $140 million. Eighty nine percent of influenza-associated severe illness cost is among risk groups. Eighty six percent of years of life lost due to influenza-associated death is among risk groups. Abstract: Background: Data on influenza economic burden in risk groups for severe influenza are important to guide targeted influenza immunization, especially in resource-limited settings. However, this information is limited in low- and middle-income countries. Methods: We estimated the cost (from a health system and societal perspective) and years of life lost (YLL) for influenza-associated illness in South Africa during 2013–2015 among (i) children aged 6–59 months, (ii) individuals aged 5–64 years with HIV, pulmonary tuberculosis (PTB) and selected underlying medical conditions (UMC), separately, (iii) pregnant women and (iv) individuals aged ≥65 years, using publicly available data and data collected through laboratory-confirmed influenza surveillance and costing studies. All costs were expressed in 2015 prices using the South Africa all-items Consumer Price Index. Results: During 2013–2015, the mean annual cost of influenza-associated illness among the selected risk groups accounted for 52.1% ($140.9/$270.5 million) of the total influenza-associated illness cost (for the entire population of South Africa), 45.2% ($52.2/$115.5 million) of non-medically attended illness costs, 43.3% ($46.7/$107.9 million) of medically-attended mild illness costs and 89.3% ($42.0/$47.1 million) of medically-attended severe illness costs. The YLL among the selected risk groups accounted for 86.0% (262, 069 /304, 867 years) of the total YLL due to influenza-associated death. Conclusion: In South Africa, individuals in risk groups for severe influenza accounted for approximately half of the total influenza-associated illness cost but most of the cost of influenza-associated medically attended severe illness and YLL. This study provides the foundation for future studies on the cost-effectiveness of influenza immunization among risk groups.